Quality Analysis of Limestone for the Raw Material of Cement Making Industry in Tangofa Village, Bungku Pesisir Sub-district, Morowali Regency - Wakila, Muhamad Hardin; Bakri, Suriyanto; Syam, Nur Ilahi (Journal of Geology and Exploration, 2023)
Morowali Regency, Central Sulawesi Province is one of the largest nickel laterite producing areas in the world, on the other hand this area also has abundant limestone potential, one of the areas that has limestone potential is the Tangofa Area, Morowali Regency. The absence of information related to the chemical composition of limestone in the area is the basis for this research. The purpose of this study was to determine the elemental and mineral content of limestone and to determine the quality of limestone as cement raw material based on CaO and MgO content. The research method was carried out with several stages, namely: literature study, field data collection, and laboratory analysis (Petrography, XRD, and XRF). From the results of petrographic analysis, it can be seen that the constituent minerals of limestone in the research area are calcite and quartz minerals, as well as the results of XRD analysis, which show the presence of calcite minerals that dominate the entire sample with a percentage reaching 100%. The results of analysis with the XRF method can be known oxide compounds constituent limestone in the study area are: CaO, MgO, K2O, PbO, Nb2O5, CuO, Sb2O3, RuO4, SnO2, and In2O3. Rh2O3, TiO2, PdO, and Ag2O. The CaO content of the three samples has a percentage of >48%, while the average MgO content does not exceed 6%, so it can be concluded that the limestone in the study area has good quality for cement raw materials.